2005
DOI: 10.1007/s10806-005-7044-3
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Biodiversity and Conservational Wildlife Quality on Danish Organic Farms for Use in Farm Management: A Multidisciplinary Approach to Indicator Development and Testing

Abstract: Organic farming is expected to contribute to conserving national biodiversity on farms, especially remnant, old, and undisturbed small biotopes, forests, and permanent grassland. This objective cannot rely on the legislation of organic farming solely, and to succeed, farmers need to understand the goals behind it. A set of indicators with the purpose of facilitating dialogues between expert and farmer on wildlife quality has been developed and tested on eight organic farms. ''Weed cover in cereal fields,'' was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Given the understanding of the key role of field margins and non-production areas in promoting biodiversity, revised organic regulations also need to consider outlining requirements for their establishment and maintenance. This will need to be done in the context of improved understanding of which non-farmed elements are more important, the relationship to landscape factors for various taxa, and even more broadly the sustainability of the farming system in relation to the agroecosystem carrying capacity within a region [4,95,101]. In general, the expansion of research examining ecological and environmental impacts of organic agriculture, sometimes tied to AES programmes (farmscaping and multifunctionality), is an important step in the evolution of organic agriculture as it shifts to a more outcomes-based system more in line with its founding principles rather than a farming system defined by permitted inputs and regulation of farming practices alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the understanding of the key role of field margins and non-production areas in promoting biodiversity, revised organic regulations also need to consider outlining requirements for their establishment and maintenance. This will need to be done in the context of improved understanding of which non-farmed elements are more important, the relationship to landscape factors for various taxa, and even more broadly the sustainability of the farming system in relation to the agroecosystem carrying capacity within a region [4,95,101]. In general, the expansion of research examining ecological and environmental impacts of organic agriculture, sometimes tied to AES programmes (farmscaping and multifunctionality), is an important step in the evolution of organic agriculture as it shifts to a more outcomes-based system more in line with its founding principles rather than a farming system defined by permitted inputs and regulation of farming practices alone.…”
Section: Resultsmentioning
confidence: 99%
“…While the above advances in understanding of the relationship between farming system, landscape and biodiversity are encouraging, we are just beginning to understand the relationship between such biodiversity and ecosystem services such as pollination, pest control, SOC storage or water quality maintenance [13,79,[93][94][95]. Under semi-arid conditions in California, Smukler et al [13] reported that environmental variables (including SOC, infiltration rates and dissolved organic C), associated with non-crop habitats on an organic farm explained the on-farm distribution of plant and soil taxa.…”
Section: Linking Biodiversity To Ecosystem Servicesmentioning
confidence: 99%
“…As our study only refers to articles listed in the Web of Science (WoS), work on practical applications of indicators may be underrepresented when published in reports, working papers, or other publications that are not listed in the WoS. This is likely why we found only a few articles where indicators were applied (e.g., de Heer et al 2005;Noe et al 2005).…”
Section: Caveats To the Interpretation Of The Resultsmentioning
confidence: 99%
“…Second, our classification was determined by our research questions (cf. Strauss and Corbin 1998;Kluge 1999) and by criteria often used to define indicators (Heink and Kowarik 2010;e.g. aggregation of ecological information, precision of correlation between indicator and indicandum, relevance of an indicator).…”
Section: Criteria Used For Assessing the Suitability Of Biodiversity mentioning
confidence: 99%
“…A reason may be that these topics differ in their local or regional significance, which should be reflected in the choice of indicators (see, e.g. Oñate et al, 2000;Noe et al, 2003).…”
Section: What Topics Should Be Included In Future Ioa?mentioning
confidence: 99%